Asymmetric Dearomatization of Naphthols via a Rh-Catalyzed C(sp2)–H Functionalization/Annulation Reaction - Zheng, Jun; Wang, Shao-Bo; Zheng, Chao; You, Shu-Li (Journal of the American Chemical Society, 2015)
A Rh-catalyzed enantioselective dearomatization of 1-aryl-2-naphthols with internal alkynes via C–H functionalization reaction was achieved. In the presence of a chiral Cp/Rh catalyst and combined oxidants of Cu(OAc)2 and air (oxygen), various highly enantioenriched spirocyclic enones bearing an all-carbon quaternary stereogenic center could be synthesized in 33–98% yields with up to 97:3 er.